2005
DOI: 10.1002/dei.1
|View full text |Cite
|
Sign up to set email alerts
|

The social participation and career decision-making of hard-of-hearing adolescents in regular classes

Abstract: This article reports on the social participation of hard-of-hearing adolescents attending integrated school settings with itinerant teacher support, and the relationship between the students' perceptions of their social participation and their social self-concept and career decision-making. As part of a mixed methods study investigating the career decision-making of hard-of-hearing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Kent [26] reported that individuals with a hearing disability were more likely to report feeling and/or experiencing loneliness than those with hearing. Many adolescents have a constant desire to be perceived as 'normal', and not having 'hearing' problems [27] because they are very aware of the power differentials between themselves and the 'dominant' hearing culture leading to marginization [28]. With improved hearing comes the chance of developing 'good' spoken language [29] and possible better health.…”
Section: Cochlear Implantmentioning
confidence: 99%
“…Kent [26] reported that individuals with a hearing disability were more likely to report feeling and/or experiencing loneliness than those with hearing. Many adolescents have a constant desire to be perceived as 'normal', and not having 'hearing' problems [27] because they are very aware of the power differentials between themselves and the 'dominant' hearing culture leading to marginization [28]. With improved hearing comes the chance of developing 'good' spoken language [29] and possible better health.…”
Section: Cochlear Implantmentioning
confidence: 99%
“…In the light of recent literature on the inclusion movement (Most, 2004;Punch and Hyde, 2005;Sari, 2005), some professionals who have experience in teaching and administrative roles in special education have maintained that teachers' attitudes towards deaf students are important factors in the success or failure of attempts to include these children in regular classrooms. Therefore, teacher education programmes need to inform teachers' attitudes towards the inclusion of deaf students in their classes by extending their information base and their teaching skills.…”
Section: Introductionmentioning
confidence: 99%
“…However, the topics under investigation were largely determined by professionals, rather than allowing the young people themselves to shape the direction of enquiry. This may mean that the young person's interpretations of and feelings about the experience are not fully explored (Punch and Hyde, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The career aspirations of teenagers with a hearing loss has been discussed in the literature since these students are more likely to encounter obstacles both in the environment and in the attitudes of others, which may negatively impact on their success (Punch and Hyde, 2005;Punch et al, 2006). These studies highlighted a number of barriers that the teenagers perceived to be related to their hearing.…”
Section: Career Barriersmentioning
confidence: 99%
See 1 more Smart Citation